Penyebaran cacing pipih New Guinea (Platydemus manokwari de Beaucham)., (Tricladida : Geoplanidae) sebagai musuh alami bekicot di daerah Manokwari - Fina Alfionita Tiong; Alexander Yaku; Frenki Arthur Paiki; Adelin Elsina Tanati; Sutiharni (Fakultas Pertanian Universitas Papua, 2020)
The purpose of this study was to determine the distribution of the New Guinea flatworm (Platydemus manokwari) as a natural enemy of snails in the Manokwari area. Observations were made at 32 locations in Manokwari area used descriptive method with interviews and direct field observations. The results showed that the distribution of the New Guinea flatworm (P. manokwari) as a natural enemy of snails was found in all locations. However, these worms have not been found directly as biological control agents for snails.